The hunger games. Mockingjay, Part 1 [videorecording (Blu-Ray)] - Lawrence, Jennifer, 1990-; Hutcherson, Josh; Hemsworth, Liam, 1990-; Harrelson, Woody; Banks, Elizabeth, 1974-; Moore, Julianne; Hoffman, Philip Seymour, 1967-2014; Tucci, Stanley; Sutherland, Donald, 1935-; Collins, Suzanne (Lionsgate, 2015)
The rebellion continues from the catacombs of District 13, as Katniss Everdeen reluctantly agrees to be the Mockingjay, the symbolic leader of the rebellion, and continue the fight against President Snow and his forces.